2017
DOI: 10.2224/sbp.6751
|View full text |Cite
|
Sign up to set email alerts
|

Positive group affective tone and employee work engagement: A multilevel investigation

Abstract: We investigated the impact of positive group affective tone on employee work engagement. Participants in the study were 74 research and development groups (324 employees and 74 group leaders) employed by high-technology companies in China. Hierarchical linear modeling results revealed a positive cross-level relationship between positive group affective tone and employee work engagement; this relationship was partially mediated by employee core self-evaluation. In addition, there was a positive relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…This conclusion has been determined by several studies that verified the effect of group positive affect on individual wellbeing. For instance, group positive affect acts as a job resource that reinforces the individual’s cognition about his/her self-worth and capabilities, as well as enhancing positive group relationship precursors of individual work engagement [ 81 ]. Moreover, group positive affect could buffer individual psychological distress as the opposite of wellbeing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion has been determined by several studies that verified the effect of group positive affect on individual wellbeing. For instance, group positive affect acts as a job resource that reinforces the individual’s cognition about his/her self-worth and capabilities, as well as enhancing positive group relationship precursors of individual work engagement [ 81 ]. Moreover, group positive affect could buffer individual psychological distress as the opposite of wellbeing.…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors also observed that those groups that experience positive affect also pursue common goals, have the skills to complete the tasks, and in turn, achieve good group performance. Finally, extending the concept of emotional contagion, Zhang, et al [ 81 ] proposed that leaders could share much more than their emotions. In fact, the authors pointed out that the leader’s psychological capital guides the development of group positive affect in their followers.…”
Section: Resultsmentioning
confidence: 99%
“…Chi, Chung, and Tsai (2011) showed that these positive leader emotions influence the group's positive affect. Also, group positive affect is associated with job performance and, in turn, on individual selfefficacy (Seong & Cho, 2014;Zhang, et al, 2017).…”
Section: Shared Transformational Leadership Perceptions and Individuamentioning
confidence: 99%
“…Desde entonces, el estudio del constructo ha proliferado con el objetivo de este entender este fenómeno grupal (Menges, y Kilduff, 2015). Concretamente, la literatura científica determina que el afecto positivo grupal tiene efectos sobre diferentes variables de resultado como el rendimiento grupal (Lee, Stajkovic, y Sergent, 2016), la creatividad grupal (Shin, 2014), eficacia colectiva (Salanova, Llorens y Schaufeli, 2011) e incluso el bienestar individual (Zhang, Zhang, y Qiu, 2017).…”
Section: El Afecto Positivo Grupal: Implicaciones Para Los Gruposunclassified